Genome wide association analysis for biomass related traits in common vetch (Vicia sativa L.) - Jin, Hui; Zhang, Jumei; Dimtrov, Yordan; Yang, Xue; Du, Ruonan; Wu, Yu-e; Chang, Danna; Zhang, Rui; Zhao, Haibin (Frontiers in Plant Science, 2025)
IntroductionCommon vetch (Vicia sativa L.) is a leguminous plant widely cultivated in Asia, Europe, and the Americas, primarily used as a forage crop and green manure.Materials and methodsTo identify loci significantly associated with biomass related traits, a genome-wide association study (GWAS) was perdormed in 172 common vetch accessions mainly from China and Europe. The single nucleotide polymorphisms (SNPs) were obtained through re-sequencing, while five biomass related traits, including the fresh weight (FW), dry weight (DW), fresh weight per plant (PFW), dry weight per plant (PDW) and plant height (PH), were evaluated across four environments.ResultsIn total, 33 loci were identified, and explain 11.6-22.5% of the phenotypic variances. Notably, among them, qPDW1.2 and qPFW1.3, qPH2.1 and qFW2.1, qDW4.1 and qFW4.1, qPH5.1 and qPH5.1, qDW6.1 and qFW6.1 are overlapped or located in the same genomic region, exhibiting pleiotropic effects on two traits, and should be prioritized in further vetch breeding programs. Additionally, all the 33 loci are novel compared with previous reports. Fifteen candidate genes for biomass related traits were identified for biomass related traits, encoding ethylene-responsive transcription factors, ABC transporter family proteins, serine/threonine-protein phosphatase, cellulose synthase, and auxin-responsive proteins. Furthermore, we successfully developed and verified a kompetitive allele-specific PCR (KASP) marker (Kasp-DW1.1) for dry weight. Accessions with more favorable alleles, superior biomass related traits and agronomic traits, eg. GLF295, GLF299, GLF313, GLF321, GLF325, GLF328, GLF329, GLF330, GLF331, GLF335, HZMC1382 and HZMC1487 are recommended as parental lines for further common vetch breeding.DiscussionThis study enhances our understanding of the genetic architecture of biomass related traits and provides available novel loci, molecular tools and outstanding varieties for improving common vetch biomass in future breeding.